Competence of the authority to accept a notification of disposal of a vehicle. Commentary on the Supreme Administrative Court Decision of 1 December 2020, I OW 97/20 - Przychodzki, Michał (Studia Iuridica Toruniensia, 2024)
The purpose of the article is to analyse the issue of the authority’s competence to accept a notification of the disposal of a vehicle. The obligation to report the disposal of a vehicle each time results from Article 78 Sec. 2 of the Road Traffic Act. The considerations in the article also concern the administrative fine related to the failure by the obligated entity to report the disposal of the vehicle within the statutory period of 30 days. Particular attention was paid to the practice of applying the provisions in question, which for a large group of entities related to the automotive industry gives rise to organizational problems resulting from the large scale of business activity. The article critically assessed the decision of the Supreme Administrative Court, which caused problems both on the side of the entities reporting the disposal of the vehicle and on the side of the authorities that accept such notifications. In conclusion, the author presented a different solution to the problem pending before the Supreme Administrative Court, based on the applicable provisions of the Act.